The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1073/pnas.88.24.11475
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent decrease in the affinity of muscarinic M1 receptors in neocortex of rhesus monkeys.

Abstract: In vitro autoradiography on tissue sections and receptor assay in cortical membrane homogenates revealed that pirenuzepine h-affinity muscarink sites (Ml) decrease in affinity in the prefrontal cortex and in other cortical areas of aged rhesus monkey (Macaca miudta). Carbachol competition experiments detected only a single, low-affinity da of sites in old monkeys, while two classes of sites (low and hh affity) were observed in young adults. The change in affinity in the aged monkeys is not accomaed by a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…For example, one study reported a modest reduction in ChAT levels in the frontal pole of aged rhesus monkeys (Wenk et al, 1989), but a subsequent study reported that the levels of this synthetic enzyme were not changed in the frontal cortex in a different cohort of aged monkeys (Wenk et al, 1991). Further, another study reported that neither M1 nor nicotinic ACh receptors are reduced with age in monkey prefrontal cortex (Wenk et al, 1989) while a subsequent study reported a significant decrease in M1 receptor binding in area 46 (Vannucchi and Goldman-Rakic, 1991). Clearly further work is required to unequivocally demonstrate whether cholinergic systems are substantially changed with age in the primate area 46.…”
Section: Neurotransmitter-specific Projections To Area 46 and Age-mentioning
confidence: 96%
“…For example, one study reported a modest reduction in ChAT levels in the frontal pole of aged rhesus monkeys (Wenk et al, 1989), but a subsequent study reported that the levels of this synthetic enzyme were not changed in the frontal cortex in a different cohort of aged monkeys (Wenk et al, 1991). Further, another study reported that neither M1 nor nicotinic ACh receptors are reduced with age in monkey prefrontal cortex (Wenk et al, 1989) while a subsequent study reported a significant decrease in M1 receptor binding in area 46 (Vannucchi and Goldman-Rakic, 1991). Clearly further work is required to unequivocally demonstrate whether cholinergic systems are substantially changed with age in the primate area 46.…”
Section: Neurotransmitter-specific Projections To Area 46 and Age-mentioning
confidence: 96%
“…Key words: antioxidants; aging; diet; dopamine; GABA; norepinephrine; striatum; cerebellum; cognitive behavior It is well known that there are numerous declines in central neuronal f unctioning that can occur in aging in the absence of neurodegenerative disease. These alterations may be manifested as a loss of neurotransmitter receptor sensitivity such as: (1) muscarinic (Amenta et al, 1989;Araujo et al, 1990;Joseph et al, 1990;Sherman and Friedman, 1990;Vannucchi, 1991;Viana et al, 1992;Yuf u et al, 1994;Egashira et al, 1996), (2) adrenergic (Burnett et al, 1990;Gelbmann and Muller, 1990;Gould and Bickford, 1997), (3) dopaminergic (Joseph et al, 1978;Roth and Joseph, 1994;Gould et al, 1996;Volkow et al, 1996;Araki et al, 1997;Z hang et al, 1997;Levine and C epeda, 1998), and (4) opioid (Dondi et al, 1992;Kornhuber et al, 1996;Nagahara et al, 1996).…”
mentioning
confidence: 99%
“…The potential discrepancy in these studies is the age range used in each study. Previous studies used animals that were only 20 years old (Wagster et al 1990) or did not include middle-aged animals (Vannucchi and Goldman-Rakic 1991). In contrast, in the current study, we used adult, middle-aged, and aged animals, and our aged animals were 22-30 years.…”
Section: Discussionmentioning
confidence: 86%